A relação entre razão e desejo e a escolha dos meios na ética aristotélica - Grison, Giovana (My University, 2026)
This dissertation examines the relation between reason and desire in Aristotelian ethics, with emphasis on the role of desires and deliberate choice. The research investigates how Aristotle conceives the cooperation between desire and reason in determining not only the ends but also the means of moral action. To this end, the study analyzes the structure of the soul and its functions, the moral and intellectual virtues, the notion of voluntariness, the definition of phronesis, and the phenomenon of akrasia. The final chapter is devoted to the classification of desires - appetite, impulse, and wish - and to the discussion of their possibilities of moral education. The investigation concludes that Aristotelian ethics is not limited to rational deliberation about means, but requires the joint formation of reason and desire, mediated by phronesis. Furthermore, it highlights that phantasia plays an indispensable role in this process, as it articulates perception, desire, and reason, thus expanding the scope of moral education. [resumo fornecido pelo autor]
A presente dissertação examina a relação entre razão e desejo na ética aristotélica, com ênfase no papel dos desejos e da escolha deliberada A pesquisa investiga de que modo Aristóteles concebe a cooperação entre desejo e razão na determinação não apenas dos fins, mas também dos meios da ação moral. Para isso, o estudo analisa a estrutura da alma e suas funções, as virtudes morais e intelectuais, a noção de voluntariedade, a definição de phronesis e o fenômeno da acrasia. O último capítulo é dedicado à classificação dos desejos - apetite, ímpeto e querer - e à discussão sobre suas possibilidades de educação. A investigação conclui que a ética aristotélica não se limita à deliberação racional sobre meios, mas exige a formação conjunta da razão e do desejo, mediada pela phronesis. Além disso, destaca-se que a phantasia desempenha papel indispensável nesse processo, ao articular sensação, desejo e razão, ampliando o alcance da educação moral. [resumo fornecido pelo autor]
Keywords: Aristóteles; Desejo; Razão; Ética; Filosofia; Desire; Reason; Ethics; Philosophy